Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T17:45:52+01:00
A) a = -0,1 b = 0,2
(a + 4b) - (5 + 2a) - (3b - 5) =
= a + 4b - 5 - 2a - 3b + 5 =
= -a + b = 0,1 + 0,2 = 0,3

b) a = 1/4 b = 2
(-a2 + 2ab - 1) + (a2 - 4ab + 5) =
= -a2 + 2ab - 1 + a2 - 4ab + 5 =
= -2ab + 4 = -2 * 1/4 * 2 + 4 =
= -1 + 4 = 3
2010-03-11T18:09:02+01:00
A)(-0,1+4*0,2)-(5+2*(-0,1))-(3*0,2-5)=(-0,1+0,8)-(5-0,2)-(0,6-5)=
= -0,1+0,8-5+0,2-0,6+5=0,3

b)〖(-0,25〗^2+2*0,25*2-1)+(〖0,25〗^2-4*0,25*2+5)=(0,0625+1-1)+(0,0625-2+5)=0,0625+3,0625=3,125

〖(-0,25〗^- oznacza 0,25 lub -0,25 jak tu widzisz do kwadratu